Pengaruh Pemberian Virgin Coconut Oil (VCO) terhadap Ruam Popok pada Bayi - Firmansyah Firmansyah; Wa Ode Sri Asnaniar; Sudarman Sudarman (Celebes Health Journal, 2019)
Abstract. This study aims to analyze the effect of giving virgin coconut oil to diaper rash on infants in Pampang Health Center Makassar City. virgin coconut oil is one of the topical therapies that can be used to treat diaper rash. The design of this study used the pre-experimental design method with the design of one group pretest posttest. The pre-experimental design method with the design of one group pretest posttest was used to see the effect of giving virgin coconut oil on diaper rash in infants, with a total sample of 15 babies. The analysis used is univariate analysis and bivariate analysis. The results of this study indicate that before giving virgin coconut oil diaper rash in infants is the most at moderate level, namely 9 respondents (60.0%) while after giving virgin coconut oil diaper rash in infants is at most mild degree, namely 8 respondents (53.3%). Wilcoxon test dependent test shows P value = 0,000 (5 0,05). So it can be concluded that there is an effect of giving virgin coconut oil to diaper rash on infants in Puskesmas Pampang 2018. This research can be applied in nursing care for babies who experience diaper rash.Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh pemberian virgin coconut oil terhadap ruam popok pada bayi di Puskesmas Pampang Kota Makassar. virgin coconut oil salah satu terapi topikal yang dapat digunakan untuk mengatasi ruam popok. Desain penelitian ini menggunakan metode pre eksperimental design dengan rancangan one group pretest posttest. metode pre eksperimental design dengan rancangan one group pretest posttest ini digunakan untuk melihat pengaruh pemberian virgin coconut oil terhadap ruam popok pada bayi, dengan jumlah sampel sebanyak 15 bayi. Analisa yang digunakan adalah analisa univariat dan analisa bivariat. Hasil penelitian ini menunjukkan bahwa sebelum pemberian virgin coconut oil ruam popok pada bayi paling banyak pada derajat sedang yaitu 9 responden (60.0%) sedangkan sesudah pemberian virgin coconut oil ruam popok pada bayi paling banyak pada derajat ringan yaitu 8 responden (53.3%). Uji wilcoxon test dependent menunjukkan nilai P value =0,000 (≤0,05). Sehingga dapat disimpulkan bahwa ada pengaruh pemberian virgin coconut oil terhadap ruam popok pada bayi di Puskesmas Pampang 2018. Penelitian ini dapat diaplikasikan dalam asuhan keperawatan pada bayi yang mengalami ruam popok.